Aplicação de um método para avaliar o desempenho de fornecedores: um múltiplo estudo de caso no setor alimentício - Silva, Milca Gonçalves (2019)
This work aims to apply a hybrid method of performance evaluation that assists in the selection and management of suppliers. Fallahpour et al. (2016) state that managing a supply chain requires its methods and tools, in order to meet this objective, this study applied a hybrid method of supplier performance evaluation that becomes specific to the company as well as to the supply chain. which is part. For this, two tools were used that fit the research needs: the MACBETH multicriteria tool (Measuring Attractiveness by a Categorical Based Evaluation), used to order the dimensions and performance aspects according to the decision makers' preference; and the supplier performance evaluation scale developed by Santos (2017), applied to identify at which level of performance suppliers are. After the applications, the results were related to analyze if the suppliers achieved performance convergent with what the company prioritizes and the recommendations regarding the actions to be taken by the focus company with its suppliers are exposed. For applicability of the method, a multiple case study was conducted with two focus companies of the food sector. For both companies, it was observed that most suppliers were positioned at level 40 of the performance scale (medium level) and did not reach some aspects of high attractiveness to the chain, however, it was suggested that companies present the results to their suppliers. and work together to partner and raise the level of performance achieved. This research presented theoretical contributions, such as the joining of two approaches never used in this configuration before; and practices, as the whole process for applying the method was detailed, and it can be applied to other companies that want a method that reflects their priorities.